Serological and genetic complement alterations in infection-induced and complement-mediated hemolytic uremic syndrome - Westra, Dineke (Pediatr Nephrol, 2016)
BACKGROUND: The role of complement in the atypical form of hemolytic uremic syndrome (aHUS) has been investigated extensively in recent years. As the HUS-associated bacteria Shiga-toxin-producing Escherichia coli (STEC) can evade the complement system, we hypothesized that complement dysregulation is also important in infection-induced HUS. METHODS: Serological profiles (C3, FH, FI, AP activity, C3d, C3bBbP, C3b/c, TCC, αFH) and genetic profiles (CFH, CFI, CD46, CFB, C3) of the alternative complement pathway were prospectively determined in the acute and convalescent phase of disease in children newly diagnosed with STEC-HUS or aHUS. Serological profiles were compared with those of 90 age-matched controls. RESULTS: Thirty-seven patients were studied (26 STEC-HUS, 11 aHUS). In 39 % of them, including 28 % of STEC-HUS patients, we identified a genetic and/or acquired complement abnormality. In all patient groups, the levels of investigated alternative pathway (AP) activation markers were elevated in the acute phase and normalized in remission. The levels were significantly higher in aHUS than in STEC-HUS patients. CONCLUSIONS: In both infection-induced HUS and aHUS patients, complement is activated in the acute phase of the disease but not during remission. The C3d/C3 ratio displayed the best discrepancy between acute and convalescent phase and between STEC-HUS and aHUS and might therefore be used as a biomarker in disease diagnosis and monitoring. The presence of aberrations in the alternative complement pathway in STEC-HUS patients was remarkable, as well. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00467-016-3496-0) contains supplementary material, which is available to authorized users.